2017
DOI: 10.1159/000453043
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Delivery Dialysis Dose on Twice-Weekly Hemodialysis Patients

Abstract: Background: Few studies have evaluated the prognostic value of dialysis dose in twice-weekly hemodialysis (HD). A single-pool Kt/V (spKt/V) over 1.70 may benefit patients receiving twice-weekly maintenance HD. Methods: This is a multicenter randomized controlled trial performed on 163 patients from 17 dialysis centers in Shanghai who were allocated to high- (n = 98) and standard-dose groups (n = 65) and followed through 96 weeks of study period. Therapeutic approaches were given to increase spKt/V to over 1.70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As for CVD mortality, a prospective study from Brazil 27 found that higher hemodialysis dose was not associated with CVD mortality among MHD patients, which was similar with our results. However, there were several previous studies showed that higher Kt/V can reduce CVD mortality in MHD patients 28 , 29 . Bloembergen WE et.al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As for CVD mortality, a prospective study from Brazil 27 found that higher hemodialysis dose was not associated with CVD mortality among MHD patients, which was similar with our results. However, there were several previous studies showed that higher Kt/V can reduce CVD mortality in MHD patients 28 , 29 . Bloembergen WE et.al.…”
Section: Discussionmentioning
confidence: 92%
“…analyzed 2479 MHD patients in America reporting that for each 0.1 higher Kt/V, the death due to cardiac causes was 12% lower 28 .The difference may be due to different races and years of research (1996 versus 2020). Similarly, a prospective randomized controlled study of twice-weekly MHD patients in Shanghai showed that the incidence of CVD in the high-dose group were decreased 29 . The difference may be due to the frequency of dialysis.…”
Section: Discussionmentioning
confidence: 93%
“…If dialysis is highly intrusive in daily life, this is obviously also related to the number of sessions per week. While there is still no agreement on the definition of “incremental” dialysis, some U.S. experts presently suggest an approach based on twice-weekly dialysis [ 18 , 19 , 83 – 85 ]. In Italy, where it is often part of an integrated approach which includes nutritional management, dialysis start generally involves one session per week, while continuing the diet prescribed in the pre-dialysis phase (usually with a moderate protein restriction, at 0.6–0.8 g/Kg/day) [ 18 – 29 , 86 ].…”
Section: The Principlist Approachmentioning
confidence: 99%
“…The slow progression of his chronic kidney disease, with good residual diuresis and lack of life-threatening episodes of ionic derangements (including hyperkalemia) further supported this approach [ 85 89 ].…”
Section: The Principlist Approachmentioning
confidence: 99%